Effect of microwave irradiation on the flexural strength and residual monomer levels of an acrylic resin repair material - Yunus, N.; Harrison, A.; Huggett, R. (Blackwell Publishing, 1994)
The degree of polymerization of an acrylic resin repair material, as established by residual monomer estimation, was compared using three different polymerization methods, i.e. bench-cure, hydroflask-cure and microwave irradiation cure. The repair strength of a conventional heat-polymerized resin was then assessed following repairs using each of these three methods. The lowest level of residual monomer was achieved with the microwave irradiation cure. It was also demonstrated that of the three methods, polymerization using microwave energy resulted in the strongest repair.